The Effect of Vehicle Noise on Hearing Thresholds in Heavy Vehicle Drivers - Shadi Pourshafie; Zohreh Izadfard; Sadegh Jafarzadeh (Iranian South Medical Journal, 2019)
Background: Noise-induced hearing loss is a common causes of sensorineural hearing loss. Drivers of heavy vehicles such as bus and truck are more exposed to the noise associated with traffic and automobiles than other members of the community, which can damage their auditory system. The present study was conducted to investigate the hearing status of heavy vehicle drivers and its relationship with factors such as age under 40 years, work experience and mean daily working hours. Materials and Methods: The present study examined the level of sensorineural hearing loss in 132 drivers, i.e. 264 ears. The drivers’ details, including age, work experience and mean daily working hours, were first recorded. Every candidate then underwent otoscopy and pure-tone audiometry at frequencies of 500, 1000, 2000, 4000 and 8000 Hz performed by an audiologist in a sound treated room. The blood pressure of these drivers was also recorded using normal techniques of blood pressure measurement. The drivers with other sensorineural hearing loss factors, including presbycusis at ages over 40 and ototoxicity, were excluded from the study. Results: The drivers’ mean age was found to be 34.0±5.097 years, their mean work experience 11.19±5.158 years and their daily working hours 5-16 hours with a mean of 9.2±56.275 hours. The highest frequency of hearing loss was observed at a frequency of 4000 Hz in about 23% of the drivers, followed the prevalence observed at 8000 Hz. No significant differences were found between hearing thresholds of intra-city and intercity drivers. Moreover, significant relationships were  observed between the level of hearing loss and factors such as age, work experience and the mean daily working hours. Conclusion: Hearing loss was observed in about one quarter of the drivers, suggesting a high frequency of noise-induced hearing loss in drivers despite the elimination of other factors contributing to sensorineural hearing loss.